Evaluation of military spending and its fffects on technological innovation in Ecuador: opportunities and limitation - Cueva-Jiménez, María Gabriela (2025)
This study analyzes the relationship between military spending and technological innovation in Ecuador, with the aim of determining whether defense investments have contributed to the country’s scientific and technological development. An econometric approach was applied, based on multiple regression models, cointegration analysis, and the Generalized Method of Moments (GMM), to evaluate data from the 2003–2023 period concerning defense expenditure, R&D investment, technological sector growth, and registered patents. The main conclusion is that there is no statistically significant relationship between military spending and increased technological innovation, suggesting that these investments have not been effectively channeled toward strengthening national technological capabilities. The study recommends redirecting military spending toward strategic dual-use innovation areas and enhancing the connection between the defense sector, academia, and the productive sector.